Luminescence from ascorbate-stabilized Er2O3 nanoparticles - Castaneda-Contreras, Jesus; Maranón-Ruiz, Virginia F.; Menéses-Nava, Marco Antonio; Chiu Zárate, Roger; Rodríguez-Rojas, Ruben A.; Ladrón de Guevara, Héctor Pérez (Photonics Letters of Poland, 2015)
We report a novel method to stabilize Er2O3 nanoparticles with ascorbate ligands. The Er2O3 nanoparticles had strong green and red emissions with sharp and well defined emission peaks. In addition, less intense UV, blue and NIR emissions were also detected. The luminescence was recorded under dynamical pumping at 525 nm, 805 nm, and 975 nm. An enhancement of the red emission is observed when the nanoparticles were pumped at 975 nm. We suggest this was due to the absorption cross sections involved in the different pumping schemes. Full Text: PDF References C. Becker, A. Olsson, R. Simpson, Erbium-Doped Fiber Amplifiers: Fundamentals and Technology, (Boston, Academic Press 1999). A. Bahtat, M.C. Marco de Lucas, B. Jacquier, B. Varvel, M. Bouazoui. J. Mugnier, J. "IR luminescence decays and radiative lifetime of the level in Er3+ doped sol-gel TiO2 planar waveguides", Opt. Mater. 7, 173 (1997). CrossRef A.J. Kenyon. "Recent developments in rare-earth doped materials for optoelectronics", Progress in Quantum Electronics 26, 225 (2002). CrossRef Q. Xiang, Y. Zhou, B.S. Ooi, Y.L. Lam, Y.C. Chan, C.H. Kam, "Optical properties of Er3+-doped SiO2-GeO2-Al2O3 planar waveguide fabricated by sol–gel processes", Thin Solid Films 370, 243 (2000). CrossRef L. Zamperdi, M. Ferrari, C. Armellini, F. Visintainer, et al. "UV-Induced Formation of [Fe(bpy)3]2+ Complex and its Confinement into Silica Fine Particles", J. Sol-Gel. Sci. Technol. 26, 103 (2003). CrossRef Z. Pan, S.H. Morgan, A. Loper, V. King, B.H. Long, W.E. Collins, "Infrared to visible upconversion in Er3+-doped-lead-germanate glass: Effects of Er3+ ion concentration", J. Appl. Phys. 77, 4688-92 (1995). CrossRef V. Sudarsan, S. Sivakumar, F.C. van Veggel, "General and Convenient Method for Making Highly Luminescent Sol−Gel Derived Silica and Alumina Films by Using LaF3 Nanoparticles Doped with Lanthanide Ions (Er3+, Nd3+, and Ho3+)", Chem. Mater 17, 4736 (2005). CrossRef P. R. Diamente, F.C. van Veggel, "Water-Soluble Ln3+-Doped LaF3 Nanoparticles: Retention of Strong Luminescence and Potential as Biolabels", J. Fluoresc. 15, 543 (2005). CrossRef K. Lunstroot, L. Baeten, P. Nockemann, J. Martens, et al. " Article Previous Article Next Article Table of Contents Luminescence of LaF3:Ln3+ Nanocrystal Dispersions in Ionic Liquids", J Phys Chem. C 113, 15322 (2009). CrossRef S. Sivakumar, F.C. van Veggel, S.P. May, "Near-Infrared (NIR) to Red and Green Up-Conversion Emission from Silica Sol−Gel Thin Films Made with La>sub>0.45Yb0.50Er0.05F3 Nanoparticles, Hetero-Looping-Enhanced Energy Transfer (Hetero-LEET): A New Up-Conversion Process", J. am. Chem. Soc. 129, 620 (2007). CrossRef J.A. Capobianco, F. Vetrone, J.C. Boyer, A. Speghini, M. Bettinelly, "Enhancement of Red Emission (4F9/2 → 4I15/2) via Upconversion in Bulk and Nanocrystalline Cubic Y2O3:Er3+", J. Phys. Chem. B 106, 1181 (2002). CrossRef J. Castaneda, M.A. Menéses-Nava, O. Barbosa, R.A. Rodr?guez, M.V. Félix, "Visible erbium luminescence in SiO2–TiO2–Er3+ sol–gel powders", Optical Materials 29, 38 (2006). DirectLink F. Auzel, "Upconversion and Anti-Stokes Processes with f and d Ions in Solids", Chem. Rev. 104, 139 (2004). CrossRef R. Aghamalyan, "Photoluminescence of erbium in polycrystalline ceramics and in crystalline film of erbium oxide", J. of Contemporary Phys. 44, 291 (2009). CrossRef Y. Choi, K. Kim, "Spectroscopic Properties of and Energy Transfer in PbO–Bi2O3–Ga2O3 Glass Doped with Er2O3", J. Am. Ceram. Soc. 82, 2762 (1999). CrossRef